Komunikasi Intelijen Dalam Melakukan Deteksi Dini Terhadap Gangguan Keamanan Dan Ketertiban Masyarakat - Gusti Bagus Eka Prasetia; Joko Prayitno; Susilo Edi Purwanto (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2019)
The West Nusa Tenggara Regional Police Mobile Brigade has a complex task in protecting the public order, of course there are efforts being made in detecting the possibility of disturbances. Surely this was done by an intelligence unit in the West Nusa Tenggara Regional Police Mobile Brigade unit. The obstacles that hampered the NTB Regional Police Brimob Intelligence Communication in Conducting Early Detection of the Threshold of Kamtibmas Disturbances in Mataram City are as follows: 1) The informant did not want to openly tell the events that had happened; 2) lack of information obtained; 3) the informant did not provide correct information; 4) difficulties in cooperating with informants; 5) lack of public awareness. The NTB Regional Police Mobile Intelligence Communication Strategy in Conducting Early Detection of the Threshold of Kamtibmas Disturbances in Mataram City as follows. 1) use espionage in gathering information material; 2) looking for as many sources of information; 3) looking for comparative information; 4) find other informants; 5) invite the community to work together in providing information. The Implications of the NTB Regional Police Brimob Intelligence Communication in Conducting Early Detection of the Threshold of Kambitmas Disturbances in the City of Mataram are as follows: 1) the more information material obtained; 2) the facts presented in the disclosure of the problem; 3) get reference information; 4) more sources to get information; and 5) the role of Bhabinkamtimas as the frontline in handling problems.